PENDEKATAN SUPERVISI PENDIDIKAN - As Shidqi, Reva Luthfiah; Trimulyo, Joko; Awaludin S., Muhamad Robie (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2024)
Improving the quality of education requires effective educational supervision. This supervision, carried out by the school principal as supervisor, aims to guide teachers in improving their abilities and performance. A variety of supervision approaches can be applied, taking into account the goals, focus and role of the supervisor. Choosing the right approach must consider teacher needs, school conditions, and educational goals. An effective supervision approach will help teachers improve the quality of education in schools.